The relationship between principals’ pedagogical leadership practices and teachers’ job performance: the role of sociodemographic characteristics - Kelemu Zelalem Berhanu (BMC Psychology)
Abstract Background Concerns about leadership style and job achievement are global priorities. Most previous investigations have concentrated on one or two of the variables rather than on the sociodemographic characteristics. To properly understand the impact of leadership styles on teacher performance, it is critical to grasp the sociodemographic characteristicsvia a holistic approach to rethinking and improving the existing level. Objective This study seeks to investigate the relationship between principals’ practice of pedagogical leadership style and teachers’ job performance by considering the effects of sociodemographic characteristics. Methods A cross-sectional survey research methodology was used, and in Ethiopia’s Gozamin and Dembecha districts, 539 teachers participated in the study. Findings Consequently, there were strong and moderate correlations between teachers’ job performance and pedagogical leadership. Sex did not significantly impact principals’ pedagogical leadership practices or teachers’ job performance. However, age and length of service significantly influenced principals’ pedagogical leadership practices but not teacher performance. Education level significantly affected teachers’ job performance but not leadership practices. Conclusions and implications - principals’ practice of pedagogical leaders plays a predictive role in teachers’ job performance. Specific sociodemographic factors also have a role in shaping leadership perceptions and performance outcomes. This study added to the body of knowledge in the fields of education and leadership about work performance and leadership style. In the end, the study inspired stakeholders in schools, government decision-makers, and other researchers to continue improving teachers’ jobs’ effectiveness by identifying factors influencing their success. These results can potentially make teachers more accessible to more students and schools and thus contribute to ensuring quality education (SDG 4).